Analysis of Human Resource Development in Enhancing Employee Performance at PT Securindo Packatama Indonesia WTC Sudirman Area - Angga Pratama; Abdurahman; Hira Maulida (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study was conducted to analyze human resource development in improving employee performance at PT Securindo Packatama Indonesia Area WTC Sudirman. This study used qualitative methods with a descriptive approach. Data collection techniques included in-depth interviews, observation, and documentation, involving one key informant and four other purposively selected key informants. The results indicate that human resource development at PT Securindo Packatama Indonesia Area WTC Sudirman has been implemented quite well through training, coaching, and supervision programs that have improved employee knowledge, skills, and discipline. However, development related to employee career aspirations and personal goals remains suboptimal. Employee performance is generally quite good, particularly in terms of work results and work behaviors that align with standard operating procedures (SOPs). However, several obstacles affect performance consistency, such as workload, shift work systems, and differences in ability between employees. This study concludes that human resource development plays a crucial role in improving employee performance, necessitating a more sustainable and varied HR development plan.